AUGMENTED REALITY SEBAGAI MEDIA PENGENALAN DAN PROMOSI UNIVERSITAS NASIONAL - Danang Aji Pangestu; Iskandar Fitri; Fauziah Fauziah (Universitas Asahan, 2020)
Abstract - Universitas Nasional is the second oldest private university in Indonesia and the oldest private university in Jakarta. But there are still many people who do not know the information about the Universitas Nasional, for that we need an application as a media introduction to the Universitas Nasional. This study utilizes augmented reality technology as an application to introduce and promote the Universitas Nasional in 3D with the Marker Based Tracking method, which utilizes the logo of the Universitas Nasional as a marker for scanning to bring up objects. The system development method in this study uses the MDLC (Multimedia Development Life Cycle) method which consists of six stages, namely concept, design, material collecting, assembly, testing, distribution. With the application of ARNAS (Augmented Reality Universitas Nasional) can be a media introduction and promotion at the Universitas Nasional. The results of the study resulted in an application in the form of displaying miniature Universitas Nasional buildings in 3D, a brief history, faculties, and room names for each block, as well as how to use the application. The ARNAS application can run well on the Android operating system.Keywords – Augmented Reality, Marker Based Tracking, MDLC, Android. Abstrak - Univeritas Nasional merupakan Universitas swasta tertua kedua di Indonesia, dan Universitas swasta tertua di Jakarta. Namun masih banyak orang yang belum mengetahui informasi tentang Universitas Nasional, untuk itu dibutuhkan sebuah aplikasi sebagai media pengenalan Universitas Nasional. Penelitian ini memanfaatkan teknologi augmented reality sebagai aplikasi pengenalan dan promosi Universitas Nasional secara 3D dengan metode Marker Based Tracking, dimana memanfaatkan logo dari Universitas Nasional sebagai marker untuk dilakukan scanning agar memunculkan objek. Metode pembangunan sistem pada penelitian ini menggunakan metode MDLC (Multimedia Development Life Cycle) yang terdiri dari enam tahap, yaitu konsep (concept), desain (design), pengumpulan bahan (material collecting), perakitan (assembly), pengujian (testing), distribusi (distribution). Dengan adanya aplikasi ARNAS (Augmented Reality Universitas Nasional) dapat menjadi media pengenalan sekaligus media promosi pada Universitas Nasional. Hasil penelitian mengasilkan aplikasi berupa menampilkan miniatur gedung Universitas Nasional secara 3D, sejarah singkat, fakultas, dan nama ruangan setiap blok, serta cara pemakaian aplikasi. Aplikasi ARNAS dapat berjalan dengan baik pada sistem operasi android. Kata Kunci - Augmented Reality, Marker Based Tracking, MDLC, Android.